2020
DOI: 10.1001/jamapediatrics.2020.0559
|View full text |Cite|
|
Sign up to set email alerts
|

Cycled Phototherapy Dose-Finding Study for Extremely Low-Birth-Weight Infants

Abstract: IMPORTANCE Cycled (intermittent) phototherapy (PT) might adequately control peak total serum bilirubin (TSB) level and avoid mortality associated with usual care (continuous PT) among extremely low-birth-weight (ELBW) infants (401-1000 g). OBJECTIVETo identify a cycled PT regimen that substantially reduces PT exposure, with an increase in mean peak TSB level lower than 1.5 mg/dL in ELBW infants. DESIGN, SETTING, AND PARTICIPANTS This dose-finding randomized clinical trial of cycled PT vs continuous PT among 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…It was previously demonstrated that unbound bilirubin may stimulate the production of endogenous ROS in platelets, thereby inducing platelet apoptosis, which is a process mediated mainly by the p38 mitogen activated protein kinase pathway; in addition, bilirubin may damage mitochondria, inhibiting the energy metabolic process of the cell and causing cell apoptosis ( 99 ). Low levels of bilirubin may also be harmful ( 8 ). Phototherapy may disrupt the protective role of the cell membrane by lowering serum bilirubin, causing production of free oxygen radicals; it may also damage lymphocyte DNA and cause a disturbance of the skin cytokine environment, which disrupts the Th2 to Th1 conversion, thus leading to allergic diseases such as asthma and allergic rhinitis ( 42 , 100 ).…”
Section: Adverse Reactions Of Phototherapy For Neonatal Hyperbilirmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously demonstrated that unbound bilirubin may stimulate the production of endogenous ROS in platelets, thereby inducing platelet apoptosis, which is a process mediated mainly by the p38 mitogen activated protein kinase pathway; in addition, bilirubin may damage mitochondria, inhibiting the energy metabolic process of the cell and causing cell apoptosis ( 99 ). Low levels of bilirubin may also be harmful ( 8 ). Phototherapy may disrupt the protective role of the cell membrane by lowering serum bilirubin, causing production of free oxygen radicals; it may also damage lymphocyte DNA and cause a disturbance of the skin cytokine environment, which disrupts the Th2 to Th1 conversion, thus leading to allergic diseases such as asthma and allergic rhinitis ( 42 , 100 ).…”
Section: Adverse Reactions Of Phototherapy For Neonatal Hyperbilirmentioning
confidence: 99%
“…Although there are several treatment schemes available in the clinical setting, blue light is generally the preferred choice for preventing the development of bilirubin encephalopathy or nuclear jaundice caused by excessive accumulation of unconjugated bilirubin ( 6 , 7 ). A high serum level of free bilirubin may cause neurotoxicity, but mildly elevated bilirubin concentrations are beneficial due to their protective antioxidant role in cell membranes, while markedly low concentrations may also be harmful ( 8 , 9 ). However, during the treatment of neonatal hyperbilirubinemia, the level of free bilirubin in the serum is decreased, which may weaken the protective effect of bilirubin on the cell membrane, thus making the cell membrane susceptible to injury and causing cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…For the standard deviation of the center random effect, a half-Normal (0,1) prior will be used. Similar neutral informative priors (19) will be used for non-binary outcomes. We will report posterior medians and 95% credible intervals for group differences and relative risks.…”
Section: Statisticalmentioning
confidence: 99%
“…Recent evidence suggests that cycled phototherapy has similar effectiveness with less photo-oxidative injury than with conventional continuous phototherapy for ELBW infants. (17)(18)(19) However, further titration of phototherapy dosing is needed for the < 750 g birthweight infants because aggressive phototherapy in comparison to conservative phototherapy had higher rates of death with a reduction in profound NDI in infants < 750 g birthweight with aggressive phototherapy but no difference when profound NDI and death were assessed as a composite. (14) For this reason, the National Institute of Child Health and Human Development (NICHD) Neonatal Research Network (NRN) is conducting a RCT to determine whether cycled versus continuous phototherapy reduces mortality for ELBW infants.…”
mentioning
confidence: 99%
“…In the Original Investigation titled “Cycled Phototherapy Dose-Finding Study for Extremely Low-Birth-Weight Infants: A Randomized Clinical Trial,” published online April 27, 2020, there was an error in the author byline. The fourth author’s middle initial should be “A,” not “F,” so his name reads “Wally A. Carlo.” This article was corrected online.…”
mentioning
confidence: 99%